2012
DOI: 10.3892/mmr.2012.1146
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vacuum freeze-drying and radiation on allogeneic aorta grafts

Abstract: Vacuum freeze-dried aorta is a satisfactory material for blood vessel grafting. Previous studies have focused on immunity, however, vacuum freeze-drying is a complicated process of heat and mass transfer, and adopting a programmed cooling process may more completely preserve the mechanical properties of the blood vessels. Irradiation, as a method of removing pathogens, lowers the antigenic activity of the blood vessels. In our study, vacuum freeze-drying combined with radiation was used as a treatment for porc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
0
2
1
Order By: Relevance
“…In contrast to the PAA treated samples, the structure of the peripheral nerve extracellular matrix appeared to be well preserved after gamma irradiation or E beam treatment. This differs to some published studies on soft tissues, such as that of Cao et al (2013) which found that irradiation of freeze-dried aortas at 20 kGy caused widespread structural damage to the extracellular matrix, including the formation of small holes and a loss of luminal structure. Bonenfant et al (2013) found that decellularised murine lungs irradiated at 60 Gy suffered significant structural damage, particularly to the alveolar region.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the PAA treated samples, the structure of the peripheral nerve extracellular matrix appeared to be well preserved after gamma irradiation or E beam treatment. This differs to some published studies on soft tissues, such as that of Cao et al (2013) which found that irradiation of freeze-dried aortas at 20 kGy caused widespread structural damage to the extracellular matrix, including the formation of small holes and a loss of luminal structure. Bonenfant et al (2013) found that decellularised murine lungs irradiated at 60 Gy suffered significant structural damage, particularly to the alveolar region.…”
Section: Discussioncontrasting
confidence: 99%
“…Induces formation of cross-links if tissue is in a wet state, leading to increases in mechanical parameters such as stiffness or mechanical strength and preserves ECM architecture. If tissue is in a dry state, scission of the collagen chains predominates and causes degradation of the ECM and negatively affects mechanical properties (Cao et al, 2013) polymyxin B) for 30 min at 37 • C, then 200 mM EDTA (pH 7.2-7.4) for 24 h at 4 • C. Each segment was then washed in hypotonic buffer (10 mM Tris-HCL, 2.7 mM EDTA, 10 KIU/mL aprotinin; pH 8.0-8.2) for 24 h at 42 • C, followed by hypotonic buffer containing 0.1% (w/v) SDS for 24 h at 42…”
Section: Sterilisation Methodsmentioning
confidence: 99%
“…The simplest method involves electrospinning a porous graft that is subsequently combined with the cells. In another strategy, porous grafts can be prepared by freeze drying [144][145][146], followed by cell diffusion. In addition, non-scaffold-based grafts can be prepared using the decellularized natural matrix technique.…”
Section: Tissue Engineering-based Structuresmentioning
confidence: 99%